Infection Control and Waste Management Plan for Malawi Policy - Malawi Government: Ministry of Health (Malawi Government, 2021)
Malawi context and objectives of the Infection Control and Waste Management Plan Malawi, one of the sub-Saharan countries, continues to face high prevalence rates of preventable diseases such as HIV and TB1. While considerable success has been made in the health sector (Health Sector Annual Report, 2010; NSP, 2011-2016), there are imminent public health concerns such as emergence of Multi Drug Resistant TB (MDR-TB), Extremely Drug Resistant TB (XDR-TB), and TB/HIV co-infection rates. According to recent WHO reports2, Southern Africa has some of the highest TB/HIV co-infection rates in the world, ranging from 50% to 77% of the estimated burden. The mining sector is one of the sectors with potential risk factors such as: occupational and surrounding communities’ exposure to silica dust; confined, poorly ventilated working environment; cramped living quarters; and high HIV prevalence. On the other hand, potential risk factors for health-care centres or hospitals (including laboratories) include: occupational exposure to TB and HIV (ibid). Since the SADC declaration on Tuberculosis (TB) in the mining sector (2012), the Government of the Republic of Malawi has not moved significantly in its commitment to elimination of TB and improvement of environmental, health and safety practices and standards in the mining sector (National TB Programme, 2015, personal communication). It is against this background that the Government of Malawi, just like other SADC member states, has embarked on a Regional TB in Mining Project (five years project), which will involve three main components namely: 1) prevention, detection and treatment of TB; 2) disease surveillance; and 3) learning knowledge and innovation. The project further involves expansion and renovations of existing health facilities including laboratories. Due to the possible impacts (which include increased infection risks and waste management challenges) of project activities, an Infection Control and Waste Management Plan is deemed necessary. Thus, this Infection Control and Waste Management Plan (ICWMP) is prepared to facilitate implementation of appropriate infection control and waste management practices across the three relevant sectors of Health, Mining and Labour, (which include work practice and administrative measures, environmental/engineering control, and use of appropriate personal respiratory protection, and improved waste collection, storage, treatment and disposal practices) to avoid infection and environmental pollution. Specifically, the objectives of this ICWMP were to 1) develop Standard Operating Procedures and Waste Management Plans for laboratories based on a quick situation assessment and 2) review and update existing documentation on health-care waste management plans under bank funded health projects. Other objectives of the assignment were to undertake gap analysis of existing situation (environmental health control aspects) within the mines and medical waste management aspects within health facilities.